Student Perceptions of CPA Profession and Its Effect on Accounting Student Motivation - Zakaria, Adam; Putra, Adrie (Lembaga Penerbitan Unversitas Esa Unggul, 2010)
This research explores the association between student perception about CPA firm and its effect of their motivation to be an auditor. Â That perception was measured by auditor career, salary and be-nefit, job flexibility, personal issues, and accounting curriculum. 114 students filled questionnaires related. The result shows that only auditor career variable which is significant at 5 % level to pre-dict student motivation becoming auditor. Â Keywords: Auditor Profession, Motivation, Accounting Curriculum